A genome‐wide association and replication study of blood pressure in Ugandan early adolescents. Issue 10 (30th August 2019) - Lule, Swaib A.; Mentzer, Alexander J.; Namara, Benigna; Muwenzi, Allan G.; Nassanga, Beatrice; kizito, Dennison; Akurut, Helen; Lubyayi, Lawrence; Tumusiime, Josephine; Zziwa, Christopher; Akello, Florence; Gurdasani, Deept; et al.
Abstract: Background: Genetic association studies of blood pressure (BP) have mostly been conducted in non‐African populations. Using the Entebbe Mother and Baby Study (EMaBS), we aimed to identify genetic variants associated with BP among Ugandan adolescents. Methods: Systolic and diastolic BP were measured among 10‐ and 11‐year olds. Whole‐genome genotype data were generated using Illumina omni 2.5M arrays and untyped variants were imputed. Genome‐wide association study (GWAS) was conducted using linear mixed model regression to account for population structure. Linear regression analysis was used to assess whether variants previously associated with BP ( p < 5.0 × 10 −8 ) in published BP GWASs were replicated in our study. Results: Of the 14 million variants analyzed among 815 adolescents, none reached genome‐wide significance ( p < 5.0×10 −8 ) for association with systolic or diastolic BP. The most strongly associated variants were rs181430167 ( p = 6.8 × 10 −7 ) for systolic BP and rs12991132 ( p = 4.0 × 10 −7 ) for diastolic BP. Thirty‐three (17 single nucleotide polymorphisms (SNPs) for systolic BP, 15 SNPs for diastolic BP and one SNP for both) of 330 variants previously identified as associated with BP were replicated in this study, but none remained significant after accounting for multiple testing. Conclusion: Variants showing suggestive associations are worthy of future investigation. Replication results suggest that variants influencing adolescent BP may overlap somewhat with those already established in previous studies, largely based on adults in Western settings. Abstract : Using the Entebbe Mother and Baby Study, we aimed to identify genetic variants associated with blood pressure (BP) among Ugandan adolescents. We conducted Genome‐wide association study (GWAS) and replication analysis for variants associated with BP. Variants showing suggestive associations are worthy of future investigation. Replication results suggest that variants influencing adolescent BP may overlap somewhat with those already established in previous studies, largely based on adults in Western settings.